2005
DOI: 10.1002/eji.200425903
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of highly immunogenic and broadly recognized mimics of the HIV‐1 CTL epitope Gag77–85

Abstract: Human immunodeficiency virus (HIV)-specific cytotoxic T lymphocytes (CTL) play an important role in HIV infection. Given the viral genetic diversity, the selection of suitable antigens and epitope variants will be important in the design of an effective vaccine. We have previously shown that combinatorial libraries are useful tools to identify epitope mimics as well as potentially cross-reactive natural sequences in protein databases. We have applied this approach to the HIV Gag p17-derived epitope SL9 (SLYNTV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Instead, it will possibly require carefully assessing the cross-reactivity potential by responses induced by subdominant variants. Although studies available to date have largely been limited to the induction of variant-specific responses in animal models, recent analyses in HIV have also documented the superior immunogenicity of certain subdominant sequence variants (12, 2527). Importantly, the inclusion of such variants in vaccine immunogen sequences may not only provide potent immunogen components but may also facilitate the screening and reliable detection of responses in cohorts with particularly high viral diversity in the circulating viral population.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it will possibly require carefully assessing the cross-reactivity potential by responses induced by subdominant variants. Although studies available to date have largely been limited to the induction of variant-specific responses in animal models, recent analyses in HIV have also documented the superior immunogenicity of certain subdominant sequence variants (12, 2527). Importantly, the inclusion of such variants in vaccine immunogen sequences may not only provide potent immunogen components but may also facilitate the screening and reliable detection of responses in cohorts with particularly high viral diversity in the circulating viral population.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 135 epitopes tested for binding, 41 did not show strong binding (IC 50 Ͼ 500 nM) to their described, restricting allele. Although this could potentially indicate wrongly assigned HLA restriction alleles (34), there are numerous examples of well-defined and frequently targeted epitopes with binding affinities Ͼ500 nM (2,7,14). In fact, when looking at epitopes with IC 50 Ͻ 500 or Ͼ 500 nM, there was no significant enrichment of rarely (Ͻ5%) or never-targeted epitopes in the group of epitopes with IC 50 Ͼ 500 nM.…”
Section: Hla Binding Affinity Is Not Associated With Immunodominancementioning
confidence: 98%
“…Studies in HLA transgenic mice confirmed the relevance of this threshold, while also indicating some correlation between affinity and the propensity to be immunogenic (12,13). Furthermore, previous studies in the human system proposed a relationship between binding affinity and the magnitude and breadth of responses for variants of a single epitope but did not examine those relationships over a heterogeneous set of epitopes (7,14). Finally, studies in the context of the more complex system of malaria infection indicate that, provided that a peptide can bind to a specific HLA molecule, subsequent antigenicity and immunogenicity may not directly correlate with the affinity of epitope binding per se.…”
mentioning
confidence: 95%
“…The principles of TCR-pMHC interactions that allow for this flexibility are not fully understood. CTL recognition-studies using peptide libraries with altered peptide ligands [9], [14][18] and pMHC-TCR structures [19], [20] allow some inferences to be made. The middle (P4–P6) part of the peptide forms the core of the interaction [9], [14][20], where the majority of amino acid substitutions (with exception of those with very similar amino acids) tend to perturb pMHC recognition.…”
Section: Introductionmentioning
confidence: 99%